Some mysterious catastrophes of the last hundred years from the point of view of non-local physics - B. V. Alexeev (Тонкие химические технологии, 2014)
Quantum solitons are discovered with the help of generalized quantum hydrodynamics. The solitons have the character of the stable quantum objects in the self consistent electric field. The theory leads to solitons as typical formations in the generalized quantum hydrodynamics. The self-consistent theory of plasmoids cannot be constructed in the frame of local physics. Particularly these effects can be considered as explanation of the existence of the stable plasmoids, lightning balls and atoms with the separated electronic shell and the positive kernel. Three well known catastrophes (Tunguska explosion, Gagarin catastrophe, accident with Malaysia Airlines flight MH370) have the same physical origin – plasmoid appearance in the Earth atmosphere.